Injectable Microporous Annealed Particle Hydrogel Based on Guest–Host‐Interlinked Polyethylene Glycol Maleimide Microgels. Issue 10 (21st August 2022) - Widener, Adrienne E.; Duraivel, Senthilkumar; Angelini, Thomas E.; Phelps, Edward A.
Abstract : Microporous annealed particle (MAP) hydrogels have emerged as a versatile biomaterial platform for regenerative medicine. MAP hydrogels have been used for the delivery of cells and organoids but often require annealing post‐injection by an external source. An injectable, self‐annealing MAP hydrogel with reversible interparticle linkages based on guest–host functionalized polyethylene glycol‐maleimide (PEG‐MAL) microgels is engineered. The effect of guest–host linkages is evaluated on different types of microgels fabricated by either batch emulsion or mechanical fragmentation methods. Batch emulsion generates small spherical microgels with controllable (10–100 μm) diameters and mechanical fragmentation generates irregular microgels with larger diameters (100–200 μm). Spherical microgels (15 μm) show self‐healing behavior and have completely recovered from high strain while fragmented microgels (133 μm) do not recover. Guest–host interactions significantly contribute to the mechanical properties of spherical microgels but have no effect on fragmented microgels. Spherical microgels are superior to the fragmented microgels for co‐injection of immune cells and pancreatic islets due to their lower force of injection, demonstrating more homogeneously distributed cells and greater cell viability after injection. Based on these studies, the spherical guest–host MAP hydrogels provide a controllable, injectable scaffold for engineered microenvironments and cell delivery applications. Abstract : Microporous annealed particles composed of interlinked microgels provide a porous and injectable alternative to bulk hydrogels. The effect of guest–host interparticle linkages on microgels made by different fabrication techniques is investigated. Microgels with guest–host interactions are self‐healing and shear‐thinning. Batch emulsion microgels have improved mechanical properties and imparted lower stresses on cells and islets during injection than mechanically fragmented gels.